2004
DOI: 10.1063/1.1786354
|View full text |Cite
|
Sign up to set email alerts
|

Sputter erosion measurements of titanium and molybdenum by cavity ring-down spectroscopy

Abstract: We report cavity ring-down spectroscopy measurements of the gas-phase number density of titanium and molybdenum sputtered by argon ions. A neodymium: yttrium-aluminum-garnet pumped optical parametric oscillator laser system is used to probe optical absorption features of titanium and molybdenum in the 375-400 nm region. For an 18 mA ion beam current, and 750 eV ions, we find that the spatially averaged number density of sputtered atoms is 6.4± 0.6ϫ 10 8 and 5.1± 0.5ϫ 10 8 cm −3 , for titanium and molybdenum, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 9 publications
(4 reference statements)
0
21
0
Order By: Relevance
“…The approach presented here uses cavity ring-down spectroscopy (CRDS), a technique which is also based on LAS but which provides significantly improved sensitivity through the use of an optical cavity. Past work has developed and validated CRDS measurements of sputtered refractory metal and boron nitride targets exposed to ion beams [23][24][25][26][27][28]. Here, we show for the first time that the method can be extended to a CRDS erosion sensor for Hall thrusters, thereby providing a new method for thruster development and life testing.…”
mentioning
confidence: 81%
“…The approach presented here uses cavity ring-down spectroscopy (CRDS), a technique which is also based on LAS but which provides significantly improved sensitivity through the use of an optical cavity. Past work has developed and validated CRDS measurements of sputtered refractory metal and boron nitride targets exposed to ion beams [23][24][25][26][27][28]. Here, we show for the first time that the method can be extended to a CRDS erosion sensor for Hall thrusters, thereby providing a new method for thruster development and life testing.…”
mentioning
confidence: 81%
“…Recently, CRDS has been used to study sputter erosion of a metallic target. (36,37) In those studies, the ion beam source and the target were housed in a vacuum chamber with a background pressure of 10 −6 -10 −7 Torr. Energetic argon ions bombarded a metallic target and elements were generated around the surface of the target.…”
Section: Combustion Flame Chemistry and Plasma Diagnosticsmentioning
confidence: 99%
“…Detailed reviews of the technique may be found in references 28 and 29. Our previous development of CRDS for sputter diagnostics has been previously described [24][25][26][27] . As shown in Fig.1, the absorbing sample is contained within a high-finesse optical cavity typically formed from two (or three) highreflectivity (R) mirrors with R ~0.9999.…”
Section: Cavity Ring-down Spectroscopymentioning
confidence: 99%
“…The work presented here builds upon our previous development of cavity ring-down spectroscopy (CRDS) for sputtering measurements [24][25][26][27] . CRDS is a highly sensitive laser-based absorption method allowing species-specific measurement of concentrations of trace species.…”
Section: Introductionmentioning
confidence: 99%